The Effect of Acidity on the Growth and Chlorophyll a Content of Latoh (Caulerpa racemosa) - Caretta Trisari Vidyaningrum; Dicky Harwanto; Seto Windarto (School of Life Sciences and Technology, Institut Teknologi Bandung, 2026)
Caulerpa racemosa is an edible green macroalga rich in chlorophyll. pH is a key environmental factor influencing seaweed performance, including growth and chlorophyll content. This study tested how pH affects growth and chlorophyll a in C. racemosa and identified the optimal pH. Experiments were conducted from November 2024 to January 2025 at the Center for Brackish Water Aquaculture (BBPBAP), Jepara, Central Java, using a completely randomised design with four treatments and three replicates: P0 (ambient pH), P1 (pH 8.25), P2 (pH 8.00), and P3 (pH 7.75). The highest biomass gain occurred at pH 8.25 (P1: 133.47 g), with the greatest specific growth rate also at pH 8.25 (P1: 3.02 % day-¹). The highest chlorophyll a content was observed under ambient pH (P0: 303.61 ± 5.56 mg L-¹). pH significantly affected both growth and chlorophyll a of C. racemosa (ANOVA, P < 0.05). Water-quality variables (dissolved oxygen, temperature, salinity, light intensity, nitrate, and phosphate) remained within ranges suitable for C. racemosa throughout the study.